A search for biologically active compounds in Acacia (Mimosaceae) species - Wickens, Kristen M. (Curtin University, 2003)
Indigenous Australians were also known to use plants for medicinal purposes. For thousands of years, Indigenous Australians have used native plants as a source of medicinal agents. Some tribes living in Central Australia still, to this day, prefer to use traditional medicines in favour of the more common and readily available western medicines. A number of plant species endemic to Australia are listed in various Aboriginal pharmacopoeias, with approximately one-third of those species belonging to two genera, Acacia and Eremophila. Of the 1100 recognised species of Acacia, approximately 900 occur in Australia. At least thirty of these species were utilised by the Indigenous Australians as a source of medicine. Extracts of 8 Acacia species were screened using four frontline bioassays. These were the brine shrimp lethality test, the crown gall tumour assays, the disc diffusion antibiotic assay and the seed germination test to determine if any of the species were biologically active. Of all the species screened, Acacia pruinocarpa showed the most promise. The species demonstrated significant activity at concentrations at low as 3.7ppm, which is well below the standard 400ppm exhibited by potassium dichromate (Sam, 1993). Acacia adsurgens and A. dictophleba were the next two promising species exhibiting activity at concentrations of 16.12ppm and 37ppm respectively. This was a trend that was also observed in the Lettuce seed germination test for allelopathy with these three species showing the most promise. Interestingly the potency of A. pruinocarpa extract decreased significantly when it was re- screened after being put through a polyamide column. It can therefore be suggested that as tannins are removed by the polyamide column, the biological activity exhibited by A. pruinocarpa is a result of the tannin content in the species (2%), although more testing is required.Both A. pruinocarpa and A. adsurgens showed promise as anti-tumour activity when used in the Crown Gall Tumour Assay (CGTA). Acacia pruinocarpa and A. adsurgens both exhibited significant activity when compared to the control producing inhibition percentages of 31% and 37% respectively. Surprisingly, only one of the Acacia species tested inhibited pathogenic growth when tested on the common pathogens Staphylococcus aureus, Streptococcus pyogens and Candida albicans. Acacia bivenosa was the only species to exhibit any activity when tested on the pathogens. This activity, however is not considered to be significant, as the species was only active against one of pathogens tested, Staphylococcus aureus. In order to be considered to be significant, a species must be active against two or more pathogens. It is however, worthy of further evaluation. Acacia species are among the large number of plants that have long been regarded sources of biological activity. This study was guided by the indigenous use of Acacia species as sources of medicine, which led to the use of front-line bioassays. All of the species tested exhibited some form of biological activity. Acacia pruinocarpa demonstrated the most promise as a source of novel biologically active compounds exhibiting activity at very low concentrations. Such compounds have not been determined as it was outside the scope of this study to identify the active constituents of this species. However, it has been suggested that tannins are responsible for eliciting some of the activity observed in A. pruinocarpa. All of the species screened in this study are worthy of further evaluation. The bioassays used in this study are good examples of front-line bioassays. All of the tests used in the study fulfil the criterion, which defines a good test.